The Impact of Effective Supply Chain Practices, Real Estate Price and Government Budget on Economic Growth: The Case of Vietnam - Phi Ha, Nguyen Ho (International Journal of Supply Chain Management, 2020)
In the context of global supply chain value, it has greatly contributed to the trade volumes, government budget utility, and promotion for economic growth. Vietnam has been as one of the fastest-growing economies in the Asian Pacific and the world with a robust 7 percent since economic reforms in 1986 till present. At the same time, the real estate market has been an enabler of economic activity by improving housing demands and enhancing economic performance. In particular, the real estate market has also been opened up for foreigners since 2015, who can buy or invest in a property in the country. This paper focuses on exploring the dynamic relationship between real estate prices, government budget, and economic growth in the case of an emerging economy. Using quarterly data covering in the period of Q1/2008 to Q4/2018 with approximately 44 observations and applying the Autoregressive Distribution Lagged (ARDL) approach, results reveal that, in both the short-run and long-run, economic growth is highly affected by fluctuations of the present, and past economic growth. Besides, there exists a long-run relationship between government budget and economic growth. Regarding real estate prices and their impact on economic growth, this study could not find any findings in this relationship in both the short and long run. The recommendations indicate that the trends of global supply value chains can strongly support economic growth in the long run.